Konsep, Problematika, dan Kebijakan Pendidikan di Eropa: Studi Komparatif Finlandia dan Jerman - Ariesi Apriyanti; Munir Munir; Nurlaila Nurlaila (Jurnal Bilqolam Pendidikan Islam, 2025)
Education systems in Europe are highly diverse, reflecting the complexity of each country's history, culture and socioeconomic conditions. This article presents a comparative study between Finland and Germany to explore the conceptual frameworks, problems and education policies implemented by the two countries. Finland stands out with its equity-based approach, student welfare and curriculum flexibility. Germany, on the other hand, promotes a vocational education system based on dualism and decentralization of education policy. This research uses a descriptive qualitative literature study method with a content analysis approach to describe the main characteristics, contemporary challenges and ongoing policy reforms. The results show that the success of the education system is largely determined by the alignment between the basic philosophy of education, local challenges, and adaptive policy strategies. In addition, the study also shows that policy adaptations that are responsive to changing times, such as technology integration and improving teacher professionalism, are important elements in responding to global demands. The findings are relevant for developing countries that want to improve the quality of national education through benchmarking successful international systems. The study provides strategic insights into how education systems can be designed to meet the challenges of social inequality, demographic change and the needs of a 21st century skills-based economy.